(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
This business plan explores the essence of Urban Spice, a small business driven by a passion for providing a unique dining experience. Originally a small project, Urban Spice has transformed into a well-known brand, demonstrating significant growth and expertise in culinary arts. The plan addresses various aspects of the business, including ethics, organizational structure, and location analysis, along with a detailed overview of the products offered and what sets them apart from competitors. With its delicious Shawarma Sisig selections and a strong commitment to customer satisfaction, Urban Spice is not just a dining destination; it’s a special place for those who appreciate flavorful food and unforgettable experiences. The business employs marketing strategies specifically designed to achieve its objectives, with a focus on its target market, which includes working individuals, families, and local millennials. The plan examines various segments such as demographic, geographic, psychographic, behavioral, and socio-economic factors for comprehensive coverage. It outlines objectives like brand awareness and customer engagement, incorporating strategies such as loyalty programs and limited-time offers. Additionally, the plan evaluates distribution channels, pricing strategies, and competitors to ensure a well-rounded approach. Projected analyses suggest that with the expected costs and sales of Urban Spice, shareholders anticipate a promising return on investment of 82.06% within the first six months of operation. To ensure the business’s sustainability and successful establishment, stakeholders plan to enhance the menu, incorporate financial insights, maintain product quality, and implement effective marketing strategies. In conclusion, this study outlines the production and operational plan for Urban Spice, situated on Luzon Avenue in Matandang Balara, Quezon City, Metro Manila. It highlights the company’s commitment to excellence, sustainability, and customer satisfaction within the competitive food industry. By thoroughly addressing business processes, transactional methods, waste management strategies, and supply chain logistics, Urban Spice proves its readiness to deliver high-quality products and services while ensuring operational efficiency and profitability. With a strong focus on maintaining high-quality standards, cultivating strategic supplier relationships, and adopting sustainable practices, Urban Spice is well-positioned to become a leading player in the market, providing unforgettable dining experiences to its diverse customer base.